Implementation Of Metacognitive Approach To Self-Regulated Learning And Mathematical Problem-Solving Skills Of Grade X Students - Diah Maya Fitrih Hrp; Arnellis Arnellis; Yerizon Yerizon; Yulyanti Harisman (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to describe the achievement of mathematical problem solving ability and learning independence of class X students of SMAN 1 Angkola Barat with a metacognitive approach. This type of research is a quasi-experiment with class X1 as the sample. The research instruments used were problem solving ability tests and learning independence questionnaires. The results of the study showed that using the Mann-Whitney U test, it was found that the problem solving ability of the experimental class had an average of 40.37 and the control class with an average of 30.63 and a sig. value of 0.0215. This means sig. <0.05. The conclusion is that the problem solving ability of students who use a metacognitive approach is better than the problem solving ability of students who use conventional learning. The learning independence of students in the experimental class obtained an average of 43.20 and the control class 27.80 and a sig. value. <0.05 or 0.001 <0.05, it is concluded that the learning independence of students taught with a metacognitive approach is better than the learning independence of students taught with conventional learning